Meningkatkan Kreativitas Siswa Kelas 1 Sd Melalui Program Semester Kurikulum Merdeka Materi SBDP - Zihan Suryani; Deti Rostika (Pusat Riset dan Inovasi Nasional, 2023)
Over time, the education system in Indonesia has undergone many changes. The curriculum in Indonesia has also changed to become an independent curriculum which is synonymous with independent learning. The method used in this research is descriptive qualitative method, and the data collected for this research is through observation. the result of this research is that the implementation of the independent curriculum in class 1 at SDN Permata Biru has been carried out according to the provisions. The independent curriculum is a curriculum that emphasizes intracurricular activities and projects to strengthen the Pancasila Student Profile (P5). Implementation of the semester program through class 1 art projects is carried out every week in semester 2. With different material each week students can produce works and study happily in accordance with the concept of independent learning. The benefits resulting from this semester program project activities are interesting to study because they are related to student creativity.